Biostratinomic analysis of Lycoptera beds from the Early Cretaceous Yixian Formation, western Liaoning, China. (9th March 2015) - Pan, Yanhong; Fürsich, Franz T.; Zhang, Jiangyong; Wang, Yaqiong; Zheng, Xiaoting
Abstract: Little is known about the palaeoenvironments of the Early Cretaceous lakes of western Liaoning. Uncertainties exist especially about the water depth, water temperatures and annual temperature fluctuations. Here, we analyse the preservation of the most abundant fish of the lakes, the teleost Lycoptera, articulated skeletons of which occur in large concentrations suggestive of mass mortality. Taphonomic features such as degree of disarticulation, orientation patterns and displacement of skeletal elements reveal distinct preservational patterns. They suggest that the water temperature was low during winter and exhibited pronounced seasonal fluctuations. The depth of the lakes was not deep. Possible causes of the fish mortality are discussed, of which anoxia is favoured. This leads to a more refined palaeoenvironmental model for these palaeolakes, which harbour one of the most important Mesozoic Lagerstätten.